2017
DOI: 10.1111/afe.12225
|View full text |Cite
|
Sign up to set email alerts
|

Micro X‐ray computed tomography suggests cooperative feeding among adult invasive bugs Leptoglossus occidentalis on mature seeds of stone pine Pinus pinea

Abstract: 1 The consumption of edible pine seeds of stone pine by the invasive Leptoglossus occidentalis represents a major concern for producers in Mediterranean countries but, to date, little knowledge is available about its feeding process on these seeds. 2 In the present study, we tested whether L. occidentalis is capable of feeding upon mature pine seeds and also estimated the impact that they may induce. 3 Sound pine seeds were offered to bugs under laboratory conditions. Seed content was analyzed via a multitechn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…X-ray imaging is a powerful tool to visualize structure and discover novel biological function in diverse systems ranging from the rhythmic pulsations of insect tracheal systems [52] to the four-dimensional morphology of large vertebrates in locomotion [53]. As a tool for non-destructive morphology, X-ray microtomography has helped to identify and classify a number of ant species, including some preserved within amber [54,55], as well as visualize the natural cavities inhabited by small insects [56,57]. Indeed X-ray imaging of artificial ant nest enclosures in the laboratory has been used to study social insect digging and building behaviours; however, using X-rays to examine these behaviours and the 3D spatial nest organization in natural conditions is technically challenging [28].…”
Section: Temnothorax X-ray Imagingmentioning
confidence: 99%
“…X-ray imaging is a powerful tool to visualize structure and discover novel biological function in diverse systems ranging from the rhythmic pulsations of insect tracheal systems [52] to the four-dimensional morphology of large vertebrates in locomotion [53]. As a tool for non-destructive morphology, X-ray microtomography has helped to identify and classify a number of ant species, including some preserved within amber [54,55], as well as visualize the natural cavities inhabited by small insects [56,57]. Indeed X-ray imaging of artificial ant nest enclosures in the laboratory has been used to study social insect digging and building behaviours; however, using X-rays to examine these behaviours and the 3D spatial nest organization in natural conditions is technically challenging [28].…”
Section: Temnothorax X-ray Imagingmentioning
confidence: 99%
“…The Western conifer seed bug, Leptoglossus occidentalis Heidemann (Heteroptera, Coreidae), is a good example of successful invaders. This polyphagous species is considered as a major pest of conifer seeds in commercial seed orchards (Lesieur et al 2014b;Strong 2016) but may also strongly affect the potential of regeneration in natural stands (Lesieur et al 2014b) as well as the production of edible seeds (Bracalini et al 2013;Farinha et al 2017). Its native range covers western North America (wNA), where it is widely distributed from British Columbia to Mexico and from the Pacific coast to Colorado (Koerber 1963).…”
Section: Introductionmentioning
confidence: 99%
“…In a similar way, it was observed that X-ray system is effi cient for assessing physical quality of Moquiniastrum polymorphum seeds (Faria et al, 2019). In mature seeds of Pinus pinea, the micro X-ray computed tomography allowed the characterization of the physical damages caused by invasive bugs (Farinha et al, 2018). Therefore, the observed results can serve as a basis for future studies specifi cally related to insect damage and other types of damage to P. gonoacantha seeds.…”
Section: Discussionmentioning
confidence: 83%